Development of aerial and belowground tubers in potato is governed by photoperiod and epigenetic mechanism - Kondhare, Kirtikumar R.; Kumar, Amit; Patil, Nikita S.; Malankar, Nilam N.; Saha, Kishan; Banerjee, Anjan K. (Plant Physiology, 2021)
Plants exhibit diverse developmental plasticity and modulate growth responses under various environmental conditions. Potato (Solanum tuberosum), a modified stem and an important food crop, serves as a substantial portion of the world's subsistence food supply. In the past two decades, crucial molecular signals have been identified that govern the tuberization (potato development) mechanism. Interestingly, microRNA156 overexpression in potato provided the first evidence for induction of profuse aerial stolons and tubers from axillary meristems under short-day (SD) photoperiod. A similar phenotype was noticed for overexpression of epigenetic modifiers-MUTICOPY SUPRESSOR OF IRA1 (StMSI1) or ENAHNCER OF ZESTE 2 (StE[z]2), and knockdown of B-CELL-SPECIFIC MOLONEY MURINE LEUKEMIA VIRUS INTEGRATION SITE 1 (StBMI1). This striking phenotype represents a classic example of modulation of plant architecture and developmental plasticity. Differentiation of a stolon to a tuber or a shoot under in vitro or in vivo conditions symbolizes another example of organ-level plasticity and dual fate acquisition in potato. Stolon-to-tuber transition is governed by SD photoperiod, mobile RNAs/proteins, phytohormones, a plethora of small RNAs and their targets. Recent studies show that polycomb group proteins control microRNA156, phytohormone metabolism/transport/signaling and key tuberization genes through histone modifications to govern tuber development. Our comparative analysis of differentially expressed genes between the overexpression lines of StMSI1, StBEL5 (BEL1-LIKE transcription factor [TF]), and POTATO HOMEOBOX 15 TF revealed more than 1,000 common genes, indicative of a mutual gene regulatory network potentially involved in the formation of aerial and belowground tubers. In this review, in addition to key tuberization factors, we highlight the role of photoperiod and epigenetic mechanism that regulates the development of aerial and belowground tubers in potato.

Historical overview of long-distance signalling in plants - Kondhare, Kirtikumar R.; Patil, Nikita S.; Banerjee, Anjan K. (Journal of Experimental Botany, 2021)
Be it a small herb or a large tree, intra- and intercellular communication and long-distance signalling between distant organs are crucial for every aspect of plant development. The vascular system, comprising xylem and phloem, acts as a major conduit for the transmission of long-distance signals in plants. In addition to expanding our knowledge of vascular development, numerous reports in the past two decades revealed that selective populations of RNAs, proteins, and phytohormones function as mobile signals. Many of these signals were shown to regulate diverse physiological processes, such as flowering, leaf and root development, nutrient acquisition, crop yield, and biotic/abiotic stress responses. In this review, we summarize the significant discoveries made in the past 25 years, with emphasis on key mobile signalling molecules (mRNAs, proteins including RNA-binding proteins, and small RNAs) that have revolutionized our understanding of how plants integrate various intrinsic and external cues in orchestrating growth and development. Additionally, we provide detailed insights on the emerging molecular mechanisms that might control the selective trafficking and delivery of phloem-mobile RNAs to target tissues. We also highlight the cross-kingdom movement of mobile signals during plant-parasite relationships. Considering the dynamic functions of these signals, their implications in crop improvement are also discussed.
Keywords: Long-distance signalling; mobile RNAs; phloem; plasmodesmata; RNA-binding proteins; small RNAs